General practitioners’ management of occupational diseases: a qualitative study in French-speaking Switzerland - Gaubicher Coline; Staeger Philippe; Danuser Brigitta; Abderhalden-Zellweger Alessia; Krief Peggy; Mediouni Zakia (BMC Primary Care)
Abstract Background Work-related health problems are a frequent reason for consultation with primary care physicians; however, few studies report on the way general practitioners’ (GPs) approach work-related health issues with their patients. Aim To investigate the practices of Swiss GPs in regarding work-related health issues presented by their patients, and to identify the resources and difficulties they faced. Methods Semi-structured interviews were conducted with 12 GPs, transcribed, and analyzed thematically. Results GPs do explore their patients' occupational field. However, the data collected are limited, even though doctors recognize that a high proportion of mental and musculoskeletal disorders may be work-related. Work-related disease insurance issues are a frequent concern in GPs everyday practice, often causing a discomfort regarding these issues. Exchanges between GPs and employers regarding work-related health issues are relatively uncommon but can yield positive outcomes when they occur. Occupational risk prevention is confined to certain high-risk exposures. When asked to express their difficulties in dealing with work-related issues, GPs mention the lack of dedicated time, insurance issues, contact with employers or the lack of it and lack of training. As for resources, GPs mainly identify specialist doctors, but still, only few of them mention occupational physicians. Conclusions Some work-related pathologies, whether frequent or serious, are not systematically investigated by GPs. This raises the question of their detection and probable under-reporting. To improve anamnesis, identification, and referral practices for occupational health issues, we suggest a targeted training for GPs, strengthened networking among stakeholders—such as occupational physicians, employers and insurers- and a revision of medical billing structures to better support the management of work-related diseases for both GPs and occupational physicians.